2022
DOI: 10.1021/acsbiomaterials.1c01525
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Biomimetic Extracellular Matrix with Silica Nanofibers: From 1D Material to 3D Network

Abstract: Biomaterials at nanoscale is a fast-expanding research field with which extensive studies have been conducted on understanding the interactions between cells and their surrounding microenvironments as well as intracellular communications. Among many kinds of nanoscale biomaterials, mesoporous fibrous structures are especially attractive as a promising approach to mimic the natural extracellular matrix (ECM) for cell and tissue research. Silica is a well-studied biocompatible, natural inorganic material that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 301 publications
1
7
0
Order By: Relevance
“…In contrast, marked and significantly enhanced upregulation for the four studied genes was detected when the HObs@SiO 2 replicas were used in combination with osteogenic media, suggesting a potential synergistic effect. Interestingly, when the osteogenic inducers were present, increased gene expression was observed for the smooth SiO 2 and the SiO 2 -MS used as controls, suggesting an effect from the silica material which has also been shown in other reports . Remarkably, no upregulation of the chondrogenic SOX9 markers was observed when the HObs@SiO 2 -based substrates were used in growth or osteogenic media, which highlights the cell type-specificity of our approach.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In contrast, marked and significantly enhanced upregulation for the four studied genes was detected when the HObs@SiO 2 replicas were used in combination with osteogenic media, suggesting a potential synergistic effect. Interestingly, when the osteogenic inducers were present, increased gene expression was observed for the smooth SiO 2 and the SiO 2 -MS used as controls, suggesting an effect from the silica material which has also been shown in other reports . Remarkably, no upregulation of the chondrogenic SOX9 markers was observed when the HObs@SiO 2 -based substrates were used in growth or osteogenic media, which highlights the cell type-specificity of our approach.…”
Section: Discussionsupporting
confidence: 81%
“…Interestingly, when the osteogenic inducers were present, increased gene expression was observed for the smooth SiO 2 and the SiO 2 -MS used as controls, suggesting an effect from the silica material which has also been shown in other reports. 38 Remarkably, no upregulation of the chondrogenic SOX9 markers was observed when the HObs@SiO 2 -based substrates were used in growth or osteogenic media, which highlights the cell type-specificity of our approach.…”
Section: Discussionmentioning
confidence: 79%
“…The major benefits of local drug delivery are the decrease of unwanted side effects and bringing down the chance of developing drug resistance in the long term. , Several studies have shown that electrospun mats and hydrogels can be studied for local drug delivery . Polymeric nanofibers have attained prominent attention for local cancer therapy due to porosity, large surface area, versatile surface modification, and high surface-to-volume ratio. , However, for drug delivery applications, several synthetic polymers, such as polycaprolactone (PCL), polyethylene oxide (PEO), polylactic acid (PLA), and polylactic- co -glycolic acid (PLGA), as well as their blends, have been utilized to make electrospun nanofibers. Polycaprolactone (PCL), one of the synthetic degradable polymers, has been extensively utilized in biomedical materials because of its biocompatibility and ability to undergo hydrolysis. …”
Section: Introductionmentioning
confidence: 99%
“…In this process, more than 200 natural and synthetic materials such as gelatin, collagen, silk fibroin, chitosan, polycaprolactone (PCL), poly‐lactic acid (PLLA), polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), and so on have been used (Keshvardoostchokami et al, 2020). Since this system can mimic the ECM and provide ideal substrates for cell proliferation and, thus, tissue development, the application of nanofibers in research and commercial considerations in various fields has increased in recent years (Keshvardoostchokami et al, 2020; Zhou et al, 2022). Some notable advantages of the electrospinning system include adjusted porosity, excellent surface/volume values, and a high ability to control the structure of nanofibers (Torres‐Martínez et al, 2018).…”
Section: Nanostructures In the Fabrication Of Nanocomposite Scaffoldsmentioning
confidence: 99%